Strengthening Cyber Resilience through IoBT Best Practices: Future Applications - Mohadib, Mohadib; Widjdi, Achmad Farid; Fathoni, Azhar; Faruq, Saddam Rasyidin Al (Formosa Journal of Science and Technology, 2025)
In today's digital era, Internet of Battlefield Things (IoBT) security has become particularly important in ensuring the success of military operations and national security. Through systematic literature observations reviewing publications from 2015 to 2024, this research aims to identify and implement best practices for securing IoBT in state protection, explore potential study topics for future development, and suggest significant IoBT security research topics for researchers. The research results show that developing strong security standards, implementing effective cybersecurity, increasing security awareness, and training, and developing a curriculum are critical to securing IoBT. Additionally, this research also identifies research opportunities that can help implement effective IoBT security strategies and inspire the development of various training curricula. These recommendations will help implement the best IoBT security practices to enhance national security and inspire academic innovation.